The Impact of panx1 on Inflammation, Immunity, and Cancer: A Comprehensive Review - Acuna-Castillo, C; Mena-Silva, J; Barrera-Ávalos, C; Blamey-Fredes, C (FRONTIERS MEDIA SA, 2025)
Pannexin 1 (Panx1) is a widely expressed membrane channel that regulates ATP release and purinergic signaling, playing essential roles in inflammation, immunity, and tumor progression. This review provides a comprehensive analysis of its structure, activation mechanisms, and its functional relevance in both innate and adaptive immunity. Panx1 has been implicated in inflammasome activation, neutrophil and dendritic cell regulation, and modulation of immune responses against infections, including SARS-CoV-2. Additionally, Panx1 plays a dual role in tumor progression, acting either as a promoter or a suppressor depending on the cellular and microenvironmental context. Pharmacological inhibition of Panx1 has shown therapeutic benefits in preclinical models of inflammatory, cardiovascular, and neurodegenerative diseases, establishing it as a promising and versatile therapeutic target. This review underscores the need for further research into Panx1 s molecular mechanisms and the development of targeted interventions to effectively address inflammatory and autoimmune diseases with precision and efficacy.